Software tool for voice disorder diagnostics - Jičínský, Milan; Mareš, Jan (Fakulta strojní. VŠB-TU Ostrava, 2019)
Causes of voice disorders may vary the same way as treatment techniques. Surgical intervention is the most used treatment method. As for not so serious cases, vocal exercises can be efficiently used instead. Still, there are only few methods to find right diagnosis or classify the scale of impact on patient’s voice. Nowadays, it is possible to extract key features (fundamental frequency, sound pressure level and less common such as cepstral coefficients, zero crossing rate or spectral energy) from patient’s speech using state-of-the-art voice processing methods. So, the software called Voice disorder diagnostician was designed. The tool that can store patient’s data and immediately provide the results of analysis.
Aplikace pro diagnostiku poruch hlasu
Keywords: voice disorder; diagnostic application; diagnostics; voice processing; microphone calibration; sound pressure level; pitch; feature extraction; porucha hlasu; diagnostická aplikace; diagnostika; zpracování hlasu; kalibrace mikrofonu; hladina akustického tlaku; extrakce příznaků